Christianity and Psychoanalysis, Part 2: Jesus the Transformer of the Super-Ego - Vitz, Paul C. (Journal of psychology and theology, 1984)
If Jesus is The anti-Oedipus (Vitz & Gartner, 1984) then his acceptance by a person should transform his or her super-ego. since the super-ego is the psychological consequence of resolving the oedipal crisis. Ways in which this transformation of the super-ego occurs are described. Emphasis is on comparing and contrasting the child's natural identification with the father with a person's super-natural identification with the Son. Similarities and differences between these identifications are discussed to clarify how the acceptance of Jesus results in a qualitatively new person.